Mind-Body Interventions for Pediatric Inflammatory Bowel Disease - Ann Ming Yeh; Anava Wren; Brenda Golianu (MDPI AG, 2017)
Pediatric inflammatory bowel disease is an autoimmune disease that causes chronic inflammation of the gastrointestinal mucosa. There is emerging evidence that the brain-gut connection affects inflammatory bowel disease (IBD) patients more than previously thought. This is evidenced by comorbid mood disorders, irritable bowel symptoms concurrent with quiescent IBD, and the potential of psychosocial stressors to trigger IBD flares. Mind-body interventions such as psychotherapy, relaxation, mindfulness, biofeedback, yoga, and clinical hypnosis offer an adjunct to standard medical treatment for IBD. We will review the current evidence base for these mind- body interventions in the treatment of pediatric IBD, illustrate a case study, and offer suggestions for future research for this promising field.